Revisiting the Transverse Cervical Artery and Vein for Complex Head and Neck Reconstruction - Prisman, Eitan; Baxter, Peter; Genden, Eric M. (Journal of Reconstructive Microsurgery Open, 2019)
Background Chemoradiotherapy is the primary treatment modality for glottic and pharyngeal subsites. Management of recurrence or second primaries in this setting is a surgical challenge requiring complex free flap reconstruction. One of the major barriers to effective reconstruction is the availability of suitable recipient vessels. We propose that the transverse cervical artery (TCA) is a viable option for complex head and neck reconstruction.Methods A retrospective chart review of 230 consecutive free tissue reconstructive cases was performed by the senior author (EG).Results Forty cases were identified that used the TCA for arterial anastomosis. Twenty-six patients had prior treatment, 13 of which had multimodality treatment. There were no microvasculature free flap failures and 5 minor flap complications.Conclusions Our experience with the TCA suggests it is a viable option for complex head and neck reconstruction, particularly in the setting of prior comprehensive neck dissection or radiation. In addition, the location of the TCA provides favorable pedicle geometry for microvascular anastomosis.
Keywords: transverse cervical artery; microvascular reconstruction; head and neck reconstruction